2012
DOI: 10.1371/journal.pone.0045201
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bacterial Vaginosis and Cervical Intraepithelial Neoplasia: Systematic Review and Meta-Analysis

Abstract: ObjectiveBacterial vaginosis (BV), the most common vaginal disorder among women of reproductive age, has been suggested as co-factor in the development of cervical cancer. Previous studies examining the relationship between BV and cervical intra-epithelial neoplasia (CIN) provided inconsistent and conflicting results. The aim of this study is to clarify the association between these two conditions.MethodsA systematic review and meta-analysis were conducted to summarize published literature on the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
2
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 49 publications
6
116
2
16
Order By: Relevance
“…Metaanalysis has shown a positive association between BV and cervical HPV infection, and the pooled prevalence of BV can be as much as 32% (Gillet et al, 2011(Gillet et al, , 2012. Therefore, the bacterial diversity in HPV-positive women is different and even more complex compared with HPV-negative women (Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalysis has shown a positive association between BV and cervical HPV infection, and the pooled prevalence of BV can be as much as 32% (Gillet et al, 2011(Gillet et al, , 2012. Therefore, the bacterial diversity in HPV-positive women is different and even more complex compared with HPV-negative women (Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We found that STIs significantly increases the risk of developing CIN 3. By-products of these pathogens uch as propionate and butyrate may damage epithelial cells, and alterations in the vaginal environment to a proinflammatory state may contribute to the development of ervical lesions (Gillet, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Большой разброс в представленных показа-телях распространенности может быть связан с включением различных групп пациенток, с демографическими вариация-ми и разными диагностическими критериями. В целом по результатам 21 исследования общая распространенность БВ составила 27,1%, особо не различаясь в развитых (28,0%) и развивающихся (23,5%) странах [3,39].…”
Section: бактериальный вагинозunclassified
“…В недавнем метаанализе, включившем более 10 000 жен-щин, доказана связь между БВ и предраковыми состояниями, а именно СIN [3].…”
Section: бактериальный вагинозunclassified
See 1 more Smart Citation